Media Preferences on Nutrition Education among Nursing Mothers in Kazaure and Yankwashi LGAs, Jigawa State - Hasiya Ibrahim Abdullahi; Hauwa Mohammed Kawo (Matondang Journal, 2026)
This study examined the media preferences of nursing mothers and their influence on nutrition education in Kazaure and Yankwashi Local Government Areas of Jigawa State, Nigeria. Adopting an explanatory sequential mixed-methods design, quantitative data were collected from 384 nursing mothers using structured questionnaires, followed by four focus group discussions to provide contextual depth. Findings revealed that radio and interpersonal communication with health workers were the most preferred and trusted sources of nutrition information, while the use of digital media remained limited due to economic, infrastructural, and literacy constraints. Regression analysis demonstrated a strong and statistically significant relationship between media preferences and nutrition education (R² = 0.931, p < .001), indicating that preferred media channels substantially shape mothers’ nutrition knowledge. Qualitative findings further showed that cultural practices, family influence, and economic realities mediate how nutrition messages are interpreted and applied. Anchored in Development Media Theory and the Health Belief Model, the study concludes that nutrition education interventions are most effective when delivered through culturally relevant, accessible, and trusted media platforms. The study recommends prioritising radio-based and community-centred communication strategies while gradually integrating digital platforms to enhance maternal and child nutrition outcomes in rural northern Nigeria.